Purification of wastewater from the ions of copper, zinc, and lead using an electrolysis method - Gomelya, Nikolai; Melnychenko, Yevheniia; Radovenchyk, Iaroslav (Eastern-European Journal of Enterprise Technologies, 2018)
Heavy metals penetrate water reservoirs as a result of natural and anthropogenic processes, thereby accumulating in soil, bottom sediment, sludge, and can further migrate into groundwater and surface water. The main sources of heavy metals penetration into natural waters are the insufficiently treated waste waters from many branches of industry. That renders relevance to the problem of removing heavy metals from wastewater in order to prevent excessive pollution of water reservoirs. Among existing methods of water purification from heavy metals’ ions at significant volumes of industrial wastewater, the electrochemical methods are rather promising. The advantage of this method is a possibility to recycle the used regeneration solutions with obtaining metals that are suitable for reuse. This paper reports results of research into the processes of electrochemical removal of heavy metals’ cations from diluted aqueous solutions in oneand twochamber electrolyzers. When conducting the study in a twochamber electrolyzer, the anode and cathode regions were separated by the anionexchanging membrane MA40. A dependence of the influence of hardness, solutions’ pH, anodic current density, and the duration of electrolysis on efficiency of the removal of heavy metals’ ions was investigated. It is shown that the ions of zinc, copper and lead are effectively removed from aqueous solutions using the electrolysis at a starting concentration of 10 mg/dm3. It was established that at the low concentrations of ions, the output for current, when reducing metals, reached (4–20)·104 % and changed little with concentration. It was determined that the efficiency of water purification from heavy metals’ ions using electrolysis increases with an increase in pH of the medium and with a decrease in the hardness of water. In the twochamber electrolyzers, these factors exert almost no effect on purification efficiency. The paper shows the prospect of using electrolysis for the selective removal of heavy metals from tap, softened and natural water. A given purification method makes it possible to not only postclean wastewater to the maximally permissible concentrations, but also enables the purification of water from natural water bodies to the quality of drinking water